INNOVATION OF LOCAL PROCESSED FOOD PRODUCTS AS AN EFFORT TO FULFILL BALANCED NUTRITION FOR CHILDREN IN BARUSARI VILLAGE - Titian Daru Asmara Tugon; Taufik Rahman Saleh; Annisa Nur Alimah; Fatimah Nur Anisa; Nadia Rahmah Pauziah; Sinta Dewi Sri Anggreini; Faradila Mursal; Aflah Afina Nurdin; Yasmin Fadillah; Silmi Sholihatun Niswah; Cusiyani Aprilia (Journal of Community Service, 2024)
Local food ingredients are very common ingredients, especially among the local community. Local food is generally easier to obtain and affordable, which usually has nutritional value that is beneficial for health. One of them is chayote and orange which have very good benefits for health. Consumption of local food is usually only processed according to the culture and traditions of the local community, which has its own recipes and processing methods. However, in the current era of globalization, there needs to be product innovation regarding the processing of local food ingredients. So that the use of local food ingredients can be managed properly in supporting agriculture, and become more attractive to consume, especially by children. Children are the next generation of the nation who play an important role in the development of the nation. Fulfillment of balanced nutrition is an important factor in the growth and development of children. This balanced nutritional condition is a major concern, especially in rural areas, in order to create quality, intelligent, and healthy human resources (HR). In addition, with the new innovation regarding the processing of local food ingredients, it will have an impact on improving the skills of mothers and children. This activity aims to provide education to the community on how to process local food ingredients into nutritious, innovative foods, and become a solution to overcome the problem of balanced nutrition, especially in rural areas.